Comparing the Trunk Endurance and Strength and Balance in Female High School Students With and Without Chronic Low Back Pain in Qazvin, Iran - Zainab Javadipoor; Aliasghar Norasteh; Hamed Babagoltabar Samakoush (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Low back pain (LBP) is a common musculoskeletal disorder whose study on adolescents is important because it causes chronic, severe, and recurrent back pain in adulthood. This study aims to compare the trunk endurance and strength and balance in female high school students with and without chronic LBP in Qazvin, Iran.Methods This is a comparative study. Participants were 196 female high school students including 98 without LBP (Age=16.22±2.79 years, Height=1.60±0.05 m, Weight=54.83±10.17 kg, BMI=21.06±3.35 Kg/m2) and 98 with LBP (Age=16.01±0.84 years, Height=1.62±0.06 m, Weight=56.76±10.50 kg, BMI=21.59±3.57 kg/m2). To measure static and dynamic balances, we used the Stork and Star balance tests, respectively. The flexion and extension strength of trunk were measured by Manual muscle test. The flexion and extension endurance were measured by 60-degree flexion test and modified Biering-Sorenson test, respectively. Data analysis was done using independent t-test done.Results There was a significant difference in the flexion strength and endurance of the trunk (P=0.005), the trunk endurance ratio (P=0.004), trunk extensor strength (P=0.02), static balance (P=0.004) and total dynamic balance (P=0.02) between the two groups.Conclusion Strengthening of trunk muscles is recommended to prevent or reduce LBP in female high school girls. Periodic examination of postural disorders and imbalance in trunk muscles is also recommended to avoid postural problems and the resulting pain.